Respon Beberapa Varietas Padi Gogo Lokal (Oryza sativa L.) Terhadap Pemupukan NPK Yang Ditanam Di Sela Tanaman Kelapa Sawit Belum Menghasilkan (TBM) (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Land use between immature oil palm plants for upland rice plantations is an alternative in spurring rice production in Riau. To increase rice productivity, NPK fertilizer is needed. The research was conducted at the Agrotechnology Education Garden, Faculty of Agriculture, Riau University, Pekanbaru. This study lasted for 4 months from January to April 2019. The study was conducted experimentally using factorial randomized block design (RBD) consisting of two factors. the first factor is NPK Mutiara fertilizer dosage (16:16:16) with a dose of 0 g.m-2, 10 g.m-2, 20 g.m-2 and 30 g.m-2. The second factor is three varieties (Kalpatali, Kuku Balam and Telur Ikan). The parameters observed were plant height, maximum number of tillers, number of productive tillers and panicle exit age. The data obtained were analyzed statistically with variance and continued with DNMRT further test at the level of 5%. The effect of of NPK fertilization significantly increased plant height, maximum number of tillers, number of productive tillers and accelerated age of panicle out of local upland rice varieties. The giving of 30 gm-2 NPK fertilizer is the best treatment to increased the growthof Kuku Balam varieties is the best of upland rice. Keywords: local varieties upland rice, NPK fertilization, oil palm plant immature.